Serotonin Syndrome Induced Tako-Tsubo Syndrome. (26th June 2022) - Lancaster, Ian; Steinhoff, Jeffrey; Mosco-Guzman, Jose; Patel, Deep
Abstract : Tako-tsubo syndrome is characterized by temporary systolic dysfunction of the left ventricle in the absence of coronary artery disease. Serotonin syndrome is a life-threatening condition associated with increased serotonergic activity in the central nervous system (CNS). We report a case of Tako-tsubo syndrome following seizures secondary to serotonin syndrome.